Travessia de famílias camponesas migrantes nordestinas: entre a morada e o assalariamento - Aroni, Rafael (2010)
The aim of this study was to analyze the impacts of migration and wage, driven by the expansion of the sugarcane sector in the Northwest Paulista, about ways to reorganize the nuclear families of migrant workers. We analyzed rearrange themselves as the gender roles played by members family before the new configuration of spaces of destination (Novo Horizonte e Mendonça/São Paulo). The investigation corresponded to the production of field data and theoretical modeldriven analytical forms of everyday resistance (Scott, 1990), taking into account the intersection between the scanning / patriarchal domination of women's work and domestic exploitation / domination of the male labor cutting cane. The methodology was oral history (tales, life histories, trajectories), and the production of a body of imagery. The data showed some changes of the patriarchal order of relations between genders, mainly on account of remuneration for work of women included in household chores in the homes of workers cut cane and other activities. We have identified opportunities to duties microrresistência female domestic tasks, namely: 1) face of male domination through the paid work outside the home, 2) speech and gestures that pointed to the renegotiation of housework. Although the patriarchal patterns prevail, they note, however, many cracks in its foundations. They noted also forms of resistance against discrimination to attribute belonging geographically to the struggle for recognition of the identity of the migrant. And practice of resistance to change work tools, in order to reduce the physical wear.